(untitled) (Global Journal of Human-Social Science, 2019)
Literature always has been playing the role of moral and ethical values it s not a mere instrument for rejoicing our nerves or entertaining us It tries to lights up our subconscious mind to bring it to the conscious stage to enable it to understand the complicacies of life and intrigue situations Thereby we become able to understand the nuances of life the good and bad Perfect idealism can be taught through literature only as literature transcends the reality it touches down on the grand imagination Moral and ethical values can be enthused better in an emotive and sensitive person literature does this phenomenon abundantly It creates the positive vibes which make the affected reader or audience crave for the adoption of values inherent literary description There is nothing better than literature which may create the ripples even in a cruel criminal for the actions have been committed He or she may repent for the crimes or wrongdoings and crave for reforms So literature has ever played an undisputed role in social reforms